Extractive metallurgy of copper - Schlesinger, Mark E. (Elsevier, 2011)
This multi-author new edition revises and updates the classic reference by William G.I. Davenport ... et al. (winner of, among other awards, the 2003 AIME Mineral Industry Educator of the Year Award "for inspiring students in the pursuit of clarity"), providing fully updated coverage of the copper production process, encompassing topics as diverse as environmental technology for wind and solar energy transmission, treatment of waste byproducts, and recycling of electronic scrap for potential alternative technology implementation. The authors examine industrially-grounded treatments of process fundamentals and the beneficiation of raw materials, smelting and converting, hydrometallurgical processes, and refining technology for a 'mine-to-market' perspective - from primary and secondary raw materials extraction to shipping of rod or billet to customers. The modern coverage of the work includes bath smelting processes such as Ausmelt and Isasmelt which have become state-of-the-art in sulfide concentrate smelting and converting. Drawing on extensive international industrial consultancies within working plants, this work describes in depth the complete copper production process, starting from both primary and secondary raw materials and ending with rod or billet being shipped to customers. The work focuses particularly on currently-used industrial processes used to turn raw materials into refined copper metal rather than ideas working 'only on paper'. New areas of coverage include the environmentally appropriate uses of copper cables in power transmission for wind and solar energy sources; the recycling of electronic scrap as an important new feedstock to the copper industry, and state-of-the-art Ausmelt and Isasmelt bath smelting processes for sulfide concentrate smelting and converting.
Keywords: Copper -- Metallurgy.; elektronické knihy; electronic books